Human Telomerase Reverse Transcriptase Gene Antisense Oligonucleotide Increases the Sensitivity of Pancreatic Cancer Cells to Gemcitabine In Vitro - Liu, Yong-ping; Ling, Yang; Hu, Yue-di; Kong, Ying-ze; Wang, Feng; Li, Peng (IntechOpen, 2012)
None